2023
DOI: 10.1161/strokeaha.123.044191
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Air Pollution Exposure and Emergency Hospital Admissions for Stroke: A Multicenter Case-Crossover Study

Xin Lv,
Wanying Shi,
Kun Yuan
et al.

Abstract: BACKGROUND: Daily exposure to ambient air pollution is associated with stroke morbidity and mortality; however, the association between hourly exposure to air pollutants and risk of emergency hospital admissions for stroke and its subtypes remains relatively unexplored. METHODS: We obtained hourly concentrations of fine particulate matter (PM 2.5 ), respirable particulate matter (PM 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A time-stratified case-crossover study conducted in the Beibu Gulf Region of China reported that an elevated NO 2 exposure of 11.2 μg/m 3 was significantly linked to an increased risk for hospitalizations of total stroke [OR: 1.040, 95% CI: 1.027–1.053] and ischemic stroke [OR: 1.052, 95% CI: 1.033–1.071], but there was no significant association with hemorrhagic stroke [ 12 ]. A multicenter case-crossover study also suggested an evident relationship between hourly exposure to NO 2 and an increased risk of hospital admissions for total stroke and ischemic stroke, while no evident impact was found on hemorrhagic stroke [ 23 ]. Another time-stratified case-crossover study among participants of the Women’s Health Initiative observed a positive association between risk for incidence of hemorrhagic stroke and NO 2 exposure, but negative association of total stroke, ischemic stroke or ischemic stroke subtypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A time-stratified case-crossover study conducted in the Beibu Gulf Region of China reported that an elevated NO 2 exposure of 11.2 μg/m 3 was significantly linked to an increased risk for hospitalizations of total stroke [OR: 1.040, 95% CI: 1.027–1.053] and ischemic stroke [OR: 1.052, 95% CI: 1.033–1.071], but there was no significant association with hemorrhagic stroke [ 12 ]. A multicenter case-crossover study also suggested an evident relationship between hourly exposure to NO 2 and an increased risk of hospital admissions for total stroke and ischemic stroke, while no evident impact was found on hemorrhagic stroke [ 23 ]. Another time-stratified case-crossover study among participants of the Women’s Health Initiative observed a positive association between risk for incidence of hemorrhagic stroke and NO 2 exposure, but negative association of total stroke, ischemic stroke or ischemic stroke subtypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%